Transformative International Relations Theory of Robert W. Cox - Lama, Sunny (GS WOW: Wisdom of Worthy Research Journal, 2024)
This paper aims to explore the concept of change in international politics as conceptualized in Robert W. Cox’s critical theory and its implications for the prospects of a post-hegemonic world order. The paper employs a critical theoretical approach, drawing on Cox’s historicist-dialectical framework to analyze the transformative potential of historical change in international relations. The findings suggest that Cox’s critical theory offers a more nuanced understanding of structural transformation, emphasizing the importance of material conditions, ideas, and institutions in shaping world orders. The paper also highlights the potential for countertendencies based on new historical blocs to emerge in response to deepening socioeconomic cleavages and the decline of Pax Americana. Drawing on Cox’s critical theory, this paper provides a comprehensive view of the potential for structural transformation of the neoliberal world order from the “bottom upwards”.